Authigenic Uranium Preservation and Bottom Water Oxygenation in the Scotia Sea - Moritz Hallmaier; Marcus Gutjahr; Jörg Lippold; Sidney R Hemming; Lukas Gerber; Michael E Weber; Anton Eisenhauer (PANGAEA, 2025)
Sedimentary uranium (U) and thorium (Th) isotopes are invaluable proxies to assess paleo export productivity and bottom water redox conditions, site-specific sediment focusing and vertical rain rates. We report authigenic uranium at IODP Site U1537 in the Scotia Sea and further provide bulk sediment δ234U, Th-normalized vertical rain rates, bulk element concentrations, porewater U concentration, biogenic barium and opal concentrations. Multiple proxies point to increased export productivity during interglacials in the Scotia Sea. During interglacials, the accumulation of authigenic U is controlled by the decomposition of substantial quantities of organic matter, caused by the high export productivity. Conversely, during glacial times, low export productivity is coinciding with low authigenic U, suggesting well-oxygenated bottom waters. Further, we gain new information on the development of Weddell Sea Deep Water export across the last termination into the Scotia Sea. The age model used for the last 150 ka is from Lu et al. (2022), and for earlier periods from Weber et al. (2022).